NEED OF INTEGRATION OF COURSE ON MEDICAL DEVICES IN UNDERGRADUATE PHARMACY CURRICULUM - Kaur, Sukhpreet (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Medical Devices are becoming indispensable part of Indian healthcare sector. Medical Devices are multi-product sector which includes various products such as implants, consumables, IVD reagents. The market of medical devices is growing tremendously but India mainly relies on imports of these devices. Indian Government has announced Promotion of Medical Devices Parks. This will encourage setting of Med Tech Industry in India. But, India has short fall of skilled manpower to work in Med Tech Industries. Pharmacists are the main authority involved in procurement and sale of these medical devices. The current curriculums of B. Pharmacy does not include Medical Devices. A course on Medical Devices should be included in curriculum. Faculty experts in pharmaceutical sciences and regulatory officers are of the view that study of medical devices should be made a mandatory discipline for all pharmacy courses approved by the Pharmacy Council of India (PCI) because, like medicines and other health technologies, these devices are also necessary for patient care. Equipping pharmacist with knowledge will benefit the pharmacist as well as improve patient care. Moreover, this will open a new avenue of jobs for the pharmacist.